Stimulation of GLP-1 Receptor Inhibits Methylglyoxal-Induced Mitochondrial Dysfunctions in H9c2 Cardiomyoblasts: Potential Role of Epac/PI3K/Akt Pathway - Nuamnaichati, Narawat; Mangmool, Supachoke; Chattipakorn, Nipon; Parichatikanond, Warisara (Frontiers in Pharmacology, 2020)
Accumulation of methylglyoxal (MG) contributes to oxidative stress, apoptosis, and mitochondrial dysfunction, leading to the development of type 2 diabetes and cardiovascular diseases. Inhibition of mitochondrial abnormalities induced by MG in the heart may improve and delay the progression of heart failure. Although glucagon-like peptide-1 receptor (GLP-1R) agonists have been used as anti-diabetic drugs and GLP-1R has been detected in the heart, the cardioprotective effects of GLP-1R agonists on the inhibition of MG-induced oxidative stress and mitochondrial abnormalities have not been elucidated. Stimulation of GLP-1Rs leads to cAMP elevation and subsequently activates PKA- and/or Epac-dependent signaling pathway. However, the signaling pathway involved in the prevention of MG-induced mitochondrial dysfunctions in the heart has not been clarified so far. In the present study, we demonstrated that stimulation of GLP-1Rs with exendin-4 inhibited MG-induced intracellular and mitochondrial reactive oxygen species (ROS) production and apoptosis in H9c2 cardiomyoblasts. GLP-1R stimulation also improved the alterations of mitochondrial membrane potential (MMP) and expressions of genes related to mitochondrial functions and dynamics induced by MG. In addition, stimulation of GLP-1R exhibits antioxidant and antiapoptotic effects as well as the improvement of mitochondrial functions through cAMP/Epac/PI3K/Akt signaling pathway in H9c2 cells. Our study is the first work demonstrating a novel signaling pathway for cardioprotective effects of GLP-1R agonist on inhibition of oxidative stress and prevention of mitochondrial dysfunction. Thus, GLP-1R agonist represents a potential therapeutic target for inhibition of oxidative stress and modulation of mitochondrial functions in the heart.